Pengaruh GCG dan CSR dalam Meningkatkan Kinerja Keuangan Bank di BEI - Anhar Firdaus; Mariana Mariana; Diana Diana; Julia Alfianti; Ryanda Saputra; Alya Maula Aztari (Owner : Riset dan Jurnal Akuntansi, 2025)
This inquire about examines the impact of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the budgetary execution of banks recorded on the Indonesia Stock Trade (IDX). Utilizing a numerous direct relapse approach, the consider assigns Return on Assets (ROA) as the subordinate variable, whereas GCG and CSR work as autonomous factors. The test determination takes after a purposive inspecting strategy, centering on banks that reliably discharge yearly and monetary reports containing GCG and CSR revelations. Some time recently testing the speculations, a few classical suspicion tests—such as multicollinearity, heteroscedasticity, and autocorrelation tests—are conducted to guarantee the model's legitimacy. The discoveries uncover that GCG emphatically and altogether impacts money related execution, while CSR does not illustrate a outstanding impact. These comes about suggest that well-implemented GCG improves benefit, whereas CSR activities may require a more key arrangement to affect money related results straightforwardly.